2016
DOI: 10.3390/nu8090564
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake Is Associated with Longevity Characterization by Metabolites and Element Profiles of Healthy Centenarians

Abstract: The relationships between diet and metabolites as well as element profiles in healthy centenarians are important but remain inconclusive. Therefore, to test the interesting hypothesis that there would be distinctive features of metabolites and element profiles in healthy centenarians, and that these would be associated with nutrient intake; the short chain fatty acids (SCFAs), total bile acids and ammonia in feces, phenol, p-cresol, uric acid, urea, creatinine and ammonia in urine, and element profiles in fing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 54 publications
(64 reference statements)
1
44
0
Order By: Relevance
“…Data for Okinawa, Sicily, Sardinia, Linda Loma (California, USA) and Bama county (China) suggest some similarity to the above conclusions from epidemiological studies of a ‘healthy’ diet, i.e. a dominance of vegetables and fruit over animal food, and of whole grains over refined carbohydrates [3538]. However, it should not be overlooked that there is a substantial contribution from other factors to healthy ageing, such as genetic background, epigenetic DNA methylation status, physical activity or daily work until high age, an active social network, and low smoking rates and alcohol consumption [39, 40].…”
Section: Overview Of Environmental and Lifestyle Factors Increasing Tmentioning
confidence: 90%
“…Data for Okinawa, Sicily, Sardinia, Linda Loma (California, USA) and Bama county (China) suggest some similarity to the above conclusions from epidemiological studies of a ‘healthy’ diet, i.e. a dominance of vegetables and fruit over animal food, and of whole grains over refined carbohydrates [3538]. However, it should not be overlooked that there is a substantial contribution from other factors to healthy ageing, such as genetic background, epigenetic DNA methylation status, physical activity or daily work until high age, an active social network, and low smoking rates and alcohol consumption [39, 40].…”
Section: Overview Of Environmental and Lifestyle Factors Increasing Tmentioning
confidence: 90%
“…In a larger cohort of 2327 individuals with metabolite data available, higher concentrations of isocitrate but not taurocholate were also associated with worse health conditions [ 72 ]. On the other hand, centenarians from the Bama County in China showed decreased levels of PCS but increased levels of fecal short-chain fatty acids (SCFAs) and total bile acids [ 73 ]. Intestinal commensal bacteria metabolize host-derived bile salts [ 74 ].…”
Section: Gut Microbiota From Birth To 100 Years and Beyondmentioning
confidence: 99%
“…Thus, changes in age-associated microbiome composition could impact on bacterial metabolism of steroid compounds and ultimately steroid hormones in peripheral tissues. Chinese centenarians have high levels of bile acids [ 73 ], suggesting a pro-longevity role. However, studies on different populations reported that increased levels of secondary bile acids are associated with an increased risk of age-associated diseases [ 72 ] and specific diseases of the gastrointestinal tract system [ 75 ].…”
Section: Gut Microbiota From Birth To 100 Years and Beyondmentioning
confidence: 99%
“…It was documented that longevity of Bama centenarians is correlated with the genetic difference, mainly the polymorphism of several related genes, such as apolipoprotein C-I [21], paraoxonase 1 [22], catechism-O-methyl transferase [23], methylene tetrahydrofolate reductase [24], peroxisome proliferatoractivated receptor delta [25], cholesterol ester transfer protein [26], microsomal triglyceride transfer protein [27], and mitochondrial DNA [28]. Alternatively, dietary fibers [29] and mineral elements [30] were also attributed to longevity although the mechanisms involved are awaiting revelation.…”
Section: Discussionmentioning
confidence: 99%